Model Structure Of Public Policy Based On Social Learning Onto Intolerant In Pandeglang District, Banten, Indonesia - Nugroho, Kandung Sapto; Rahayu, Rahayu; Adnan, Muhammad; Warsono, Hardi (ijd-demos, 2020)
This research aims to design a model of public policy drafting in governance that can ensure the continuity of democratic principles. The principle of justice and equality both economically, socially, and politically are these foundations of democracy. If this principle is applied in the running of the government management process will be able to guarantee every individual citizen so that good governance is achieved. This approach of research with Positivistic with survey method through a closed questionnaire that has been done test validity, normality, reliability of the questionnaire to the leader of regional device organization in Pandeglang District government environment. This research will contribute to the mechanism of public policy retrieval with the primary mission to minimize potential conflicts. Please note that in 2011 in Pandeglang District, there had been a religious conflict in the case of Cikeusik Ahmadiyah, and by Tirto.id, Banten declared as the Intolerant region. The results of this study show that government bureaucracy in providing public services such as education, health, and religion has paid attention to the aspects of equalization and social justice, but it requires acceleration for bureaucracy related to the challenges of growing public problems. The influx of the 4.0 Industrial Revolution is aligned with the disruption era, the bureaucracy has to make adjustments to provide public service with typical generations of baby boomers, generation X, millennial generation even now already on Z generation and Alpha generation are already native to the Internet.Â Penelitian ini bertujuan untuk merancang model penyusunan kebijakan publik dalam tata pemerintahan yang dapat menjamin kelangsungan prinsip demokrasi. Prinsip keadilan dan kesetaraan baik secara ekonomi, sosial, dan politik adalah fondasi demokrasi tersebut. Apabila prinsip ini diterapkan dalam menjalankan proses pengelolaan pemerintahan akan dapat menjamin setiap individu warga negara sehingga tercapai tata pemerintahan yang baik. Pendekatan penelitian ini bersifat positivistik dengan metode survei melalui angket tertutup yang telah dilakukan uji validitas, normalitas, reliabilitas angket kepada pimpinan perangkat perangkat daerah di lingkungan Pemerintah Kabupaten Pandeglang. Penelitian ini akan berkontribusi pada mekanisme pengambilan kebijakan publik dengan misi utama meminimalisir potensi konflik. Perlu diketahui bahwa pada tahun 2011 di Kabupaten Pandeglang pernah terjadi konflik agama dalam kasus Ahmadiyah Cikeusik, dan oleh Tirto.id, Banten dinyatakan sebagai Daerah Intoleran. Hasil penelitian ini menunjukkan bahwa birokrasi pemerintah dalam memberikan pelayanan publik seperti pendidikan, kesehatan, dan agama telah memperhatikan aspek pemerataan dan keadilan sosial, namun diperlukan percepatan birokrasi terkait dengan tantangan permasalahan publik yang semakin berkembang. Masuknya Revolusi Industri 4.0 ini selaras dengan era disrupsi, birokrasi harus melakukan penyesuaian untuk memberikan pelayanan publik dengan tipikal generasi baby boomer, generasi X, generasi milenial bahkan sekarang sudah ada generasi Z dan generasi Alpha sudah asli Internet.Â